Recreational Angler Perspectives of Nonnative Fishes. Issue 2 (3rd March 2016) - Edwards, Christopher J.; Heinen, Joel T.; Rehage, Jennifer S.
ABSTRACT: Although fish invasions have implications for conservation and resource management, research on public attitudes toward nonnative fishes is lacking. We surveyed boat and canal bank recreational anglers in the Everglades to assess their awareness, preferences, and perspectives of native versus nonnative fishes. Our findings showed that 79% of anglers were aware of the presence of nonnative fishes, and overall awareness was positively affected by the frequency of fishing, and years of angler experience at study sites. Frequency of fishing had a stronger effect on canal bank anglers. Boat anglers had higher awareness of nonnatives, higher familiarity with "nonnative" terminology, and expressed greater preferences for native fish. Most anglers favored native species (72% preference), and targeted native fishes, particularly Florida Largemouth Bass (66%). Overall, findings show that despite the prevalence of nonnative species, anglers favored native fishes and supported native fish conservation.